Thermal neutron detection by entrapping 6LiF nanocrystals in siloxane scintillators. (May 2015) - Carturan, S M; Marchi, T; Maggioni, G; Gramegna, F; Degerlier, M; Cinausero, M; Palma, M Dalla; Quaranta, A
Abstract: Exploiting the long experience in design and production of scintillating mixtures based on siloxane matrices with combinations of primary dye and waveshifter, a first set of 6 LiF loaded scintillator disks has been produced. The synthesis is herein described and reported, as well as preliminary results on their light response towards thermal neutrons. The preservation of transparency and mechanical integrity of the scintillator material is challenging when introducing the inorganic salt LiF which is a "foreign body" to the organic polysiloxane host matrix Different strategies such as synthesis of nanoparticles and surface functionalization have been pursued to succeed in the entrapment of the neutron converter whilst maintaining moderate light output, optical transparency and flexibility of the base scintillator.